PELAKSANAAN SENAM KAKI DM BAGI KAKI PENYANDANG DM DUSUN KWARASAN YANG BERADA DI DESA NOGOTIRTO, GAMPING SLEMAN YOGYAKARTA - Agus Sarwo Prayogi; Induniasih . (ABDIKEMAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Diabetes Mellitus is a non-communicable disease that is increasing in number in the future due to lifestyle changes. These non-communicable diseases are the main killers in Indonesia compared to infectious diseases. Complications of Diabetes Mellitus include eye disorders (retinopathy), kidney disorders (nephropathy), blood vessel disorders (vasculopathy), and abnormalities in the legs. Feet are limbs that get less attention because they are far from sight and eye observation. Management of prevention of complications in patients with Diabetes Mellitus is not only limited to counseling. Direct intervention in the form of foot exercises for people with DM aims to improve blood circulation so that nutrients to the tissues run more smoothly. Community Service Activities carried out in Kwarasan Hamlet, Nogotirto, Gamping, Sleman were carried out 8 times; The target audience in community service for people with diabetes mellitus is 12 people in Kwarasan Village Nogotirto Gamping Sleman; carried out by home visits, namely: conducting assessments, measuring blood sugar at time, exercise foot exercises for Diabetes Militus; Supervision of Diabetus Militus foot gymnastics, Diabetus Militus foot exercises performed 4 times; Supervision of diabetic foot exercise is carried out 2 times for each person with diabetes mellitus; On the sixth week of conducting an assessment, measuring blood sugar while, supervising diabetic militus foot exercises; as well as providing illustrated leaflets containing steps for diabetic foot exercise and termination. Diabetus Militus foot exercise is performed by people with diabetes mellitus to prevent injuries and help improve blood circulation in the legs. Leg exercises can help improve blood circulation and strengthen the small muscles of the feet and prevent foot deformities. In addition, it can increase the strength of the calf muscles, thigh muscles, and also overcome the limitations of joint movement.